Port authority corporate social responsibility (CSR) and perceptions of entrepreneurs and port enterprises - Boza, José; González, Matías M.; de León, Javier (Cooperativismo & Desarrollo, 2017)
Introduction: The Spanish Ports Act of 2010 (33/2010) is one of the ground-breaking laws that obliges Port Authorities, which are public institutions, to pursue sustainable development, justify the actions undertaken and disclose their results in annual Sustainability Reports. Methodology: Structural Equation Models (sem) were used with an unobserved dependent variable: “the values or transmission of the port authority’s values” and two latent explanatory variables: “Relational climate with port authorities” and “Environmental conditions in the port”; the parameters have been estimated by the maximum likelihood procedure. Results: The results of the Structural Equation Model (sem) applied in this study confirm the existence of a direct and positive relationship between the climate of relations and the port authority’s ethical values, and an additional direct effect of the environmental value on the endogenous variable, which produces an unexpected negative value. Conclusions: The results show that the Social Responsibility report is a necessary tool to explain how the Port Authorities carry out Social Responsibility actions, but it is also perceived that they are of little practical use, as they are too technical and non-binding for the stakeholders.